Gaya Belajar Dalam Fenomena Pembelajaran Menyimak Siswa Di Sekolah Dasar - Onnyvia Novitasandra; Siti Masfuah; Nur Fajrie (Mathematics Education Study Program, 2025)
This study aims to describe the factors that influence the learning style of students' listening skills in elementary schools. The focus of this study is to describe all factors that cause the influence of the learning style of listening skills. The type of research is a qualitative phenomenological type by comparing the existing phenomena according to the original. Data collection techniques use observation and interviews. Interviews are given in the form of structured interview guidelines face to face to informants. Data analysis was carried out using the DPA (Descriptive Phenomenology Analysis) method. The results of the study showed that there were five main factors in influencing the learning style of listening skills including (1) psychological factors; (2) emotional factors; (3) fatigue factors; (4) learning environment; and (5) teacher teaching methods